Managing Educational Costs at SDIT Insan Cermat - Ara Hidayat; Ende Widiyana; Fahri Sahrul Ramadhan (al-Afkar, Journal For Islamic Studies, 2025)
This research is based on the condition of education financing management at Insan Cermat Integrated Islamic Elementary School (SDIT), which is the main support for the sustainability of educational activities at the school. This study aims to analyze the effectiveness of the use of school-owned financial resources, the level of responsibility and transparency in financial management, minimize errors in fund management, and understand the contribution of school finance to improving the quality of learning in the classroom. The approach used is a qualitative method with a single case study type that focuses on the management of education financing at SDIT Insan Cermat. Data were collected through documentation and interviews. The results showed that SDIT Insan Cermat does not experience financial difficulties in obtaining education funds, and their use is directed for educational purposes. The principal works optimally with the treasurer, so that a number of school programs can run well. The accountability system implemented reflects the school's responsibility, while transparency is realized by displaying the report on the use of funds on the notice board so that it can be accessed by all parties. The utilization of school finances is also proven to support the improvement of the quality of learning in the classroom, marked by the fulfillment of various important facilities and infrastructure. Based on the results of this study, it can be concluded that the management of education financing at SDIT Insan Cermat has been implemented according to good procedures.